A Double-Blind, Placebo Controlled, Multicentre Study of the Efficacy And Safety of 5-Aminosalicylic Acid Tablets in the Treatment of Ulcerative Colitis. (1st November 1990) - Sutherland, LR; Robinson, M; Onstad, G; Peppercorn, M; Greenberger, N; Goodman, M; Martin, F
Abstract : This double-blind, placebo controlled, multicentre, parallel trial assessed the efficacy of two oral doses of a new formulation of 5-aminosalicylic acid (5-ASA) targeted to release in the cecum which was given for six weeks to 136 patients with active ulcerative colitis. Seven centres participated (two Canadian, five American). Patients were randomly assigned to one of three treatment groups (4 g 5-ASA, 2 g 5-ASA or placebo). Medication was dispensed as 250 mg identically appearing tablets containing either 5-ASA or placebo to be taken four times a day. Subjects were assessed at baseline and after three and six weeks of treatment. Assessments included a disease activity index, physician's global assessment and flexible sigmoidoscopy. Compliance was assessed through pill count. A total of 136 patients participated ( 4 7 on 4 g 5-ASA, 45 on 2 g 5-ASA, and 44 on placebo). The three groups were similar in terms of age, weight, distribution of disease, extent of disease, and previous use of steroids or sulphasalazine. Ninety patients completed the six week study. Of the 46 dropouts, 38 (82.6%) left because of insufficient efficacy ( most on either place ho or 2 g 5-ASA), four (8.7%) had adverse reactions (all on 5-ASA), the remaining four (8.7%) left for reasons not related to their ulcerative colitis. The disease activity index represents a composite score ( maximum of 12) with categories for number of daily stools, presence of bleeding, abdominal pain and physician's assessment of disease activity. Patients who received 4 g 5-ASA daily demonstrated significant declines in disease activity index within three weeks of therapy and maintained improvement until the end of the stuuy. Although disease activity index declined for patients receiving 2 g 5-ASA daily, these changes did not reach statistical significance when compared to placebo-treated patients. On a five point scale (much improved, somewhat improved, unchanged, somewhat worse, much worse) the physician's global assessment mirrored the changes in disease activity index. Patients randomized to receive 4 g 5-ASA tablets were consistently noted as being either much or somewhat improved compared to placebo-treated patients. Side effects were few and minor and 52% (4 g 5-ASA), 42% (2 g 5-ASA) and 37% (placebo) of patients had no complaints. Headache was the most commonly cited adverse reaction for 6.9% (4 g 5-ASA) and 9.4% (2 g 5-ASA) of treated patients but 3.5% of placebo-treated patients also complained of headache. In conclusion in this randomized double-blind, placebo controlled study, patients with active ulcerative colitis randomized to 4 g 5-ASA per day noted improvement in disease activity as measured by disease activity index and physician's global assessment when compared to placebo-treated patients. ln contrast, patients who received 2 g 5-ASA daily did not demonstrate significant differences compared to the placebo group.